ANALYSIS OF PURCHASING DECISIONS ON THE SHOPEE MARKETPLACE: A STUDY OF THE PEOPLE OF SUMEDANG CITY - Fadila Nurfauzia; Megah Dewi Anggini; R.M Esa Febriansyah (PT. Berkah Digital Teknologi, 2026)
Purpose: This study aims to analyze the purchasing decision behavior of the people of Sumedang City on the Shopee marketplace and identify the key factors influencing these decisions, including ease of use, promotions, consumer reviews, trust, product quality, and payment methods. The findings are expected to provide insights into consumer behavior and support the development of effective digital marketing strategies. Research Methodology: This study employed a qualitative research design with a descriptive approach to explore purchasing decision behavior among the people of Sumedang City on the Shopee marketplace. The research was conducted in Sumedang City, where online marketplace usage is relatively high. Data were collected from primary and secondary sources. Primary data were obtained through in-depth, semi-structured interviews with selected informants who had prior experience shopping on Shopee, while secondary data were gathered from academic literature, journals, and relevant reports related to consumer behavior and e-commerce. ensure data validity, triangulation of sources and methods was applied, along with member checking. Ethical considerations were maintained throughout the research by ensuring voluntary participation, informed consent, and confidentiality of informants’ identities. Results: The findings indicate that purchasing decisions among the people of Sumedang City on Shopee are influenced by product confidence, purchasing habits, recommendations from others, and the tendency to make repeat purchases. Overall, the people of Sumedang City have positive shopping experiences on Shopee, as the platform is considered practical, efficient, and offers various promotional benefits. However, some challenges remain, such as delivery delays and discrepancies between product descriptions and actual products received. This study is expected to contribute to the development of digital marketing strategies and serve as a reference for local business actors in optimizing the use of marketplaces. Limitations: This study is limited by its qualitative approach and the relatively small number of informants, which may restrict the generalizability of the findings beyond the context of Sumedang City. In addition, the research focuses on a single marketplace platform (Shopee), so consumer behavior on other e-commerce platforms may differ. Contribution: This study contributes to marketing management, consumer behavior, and digital commerce by providing insights into purchasing decisions in a local Indonesian context. The findings are useful for e-commerce platforms, online sellers, and researchers in developing and studying digital marketing strategies and online consumer behavior. Keywords: purchasing decision, marketplace, Shopee, consumer behavior, Sumedang City